Pengaruh Kompres Hangat dan Pijat Oksitosin dalam Meningkatkan Kelancaran Pengeluaran ASI Pasca Persalinan - Yuni Astuti; Erni Suprapti; Tuti Anggarawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The postpartum period, which begins with the delivery of the placenta and ends when the reproductive organs return to their pre-pregnancy state, lasts approximately 6-8 weeks. During this period, many mothers face challenges related to breast milk production, resulting in insufficient or absent milk flow. This condition, if untreated, can hinder the breastfeeding process and affect both maternal and infant health. To address these challenges, several interventions such as warm compresses and oxytocin massage have been explored. The aim of this study was to assess the effectiveness of these two methods in improving breast milk flow among postpartum mothers. A quasi-experimental design was employed, utilizing a non-equivalent control group with pre-test and post-test measurements. The study targeted postpartum mothers who were experiencing difficulties with breast milk production. Purposive sampling was applied to select participants who met the inclusion criteria. The results showed significant differences between the effects of warm compresses and oxytocin massage on postpartum breast milk flow, with a p-value of 0.002 (<0.05), indicating that both methods positively influenced milk production. However, it was found that oxytocin massage had a more pronounced effect on milk flow compared to warm compresses. These findings suggest that oxytocin massage may be a more effective intervention for enhancing breast milk production in postpartum mothers, thus providing valuable information for healthcare professionals aiming to support new mothers in the breastfeeding process. The study also highlighted the importance of personalized care based on individual needs. Further research is recommended to investigate the long-term impact of these interventions and their broader application in various postpartum care settings. Additionally, exploring other complementary approaches could offer a more comprehensive strategy for managing breastfeeding difficulties in the postpartum period.